KUALITAS PELAYANAN DAN FASILITAS TERHADAP KEPUASAN PELANGGAN MELALUI KEPUTUSAN PEMBELIAN PADA WORK COFFEE DI UNIVERSITAS BHAYANGKARA JAYA KAMPUS BEKASI - amanda, Putri; Ali, Hapzi; Hadita, Hadita; Sawitri, Ni Nyoman; Navanti, Dovina (SINERGI : Jurnal Riset Ilmiah, 2025)
Service Quality and Facilities on Customer Satisfaction through Purchasing Decisions at Work Coffee at Bhayangkara Jaya University Bekasi Campus. This study aims to explore the effect of service quality and facilities on customer satisfaction through purchasing decisions. This study uses a quantitative method with a sampling technique, namely purposive sampling. The research sample consisted of 126 selected respondents. The research instrument is a questionnaire that has been tested for validity and reliability. Data analysis was carried out using the Partial Least Squares (PLS) method with the help of SmartPLS 4.0 software. The results of the research conducted at work coffee are as follows: 1) Service Quality variables have a positive and significant effect on Purchasing Decisions; 2) Facility variables have a positive and significant effect on Purchasing Decisions; 3) Service Quality variables have a positive and significant effect on Customer Satisfaction; 4) Facility Variables have a positive and significant effect on Customer Satisfaction; 5) Purchasing Decisions have a positive and significant effect on Customer Satisfaction.